EFFECT OF THE CULTURAL AND NATURAL ENVIRONMENT ON THE DESIGN OF GREEN URBAN SPACES FOR THE SALHIA COMPLEX - Sundus A. A.; S.N.Jasim; S. M. Al-kaissi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to identify the basic principles and design considerations (cultural and natural) that can be relied upon in the urban landscape design for vertical residential complexes in Baghdad city. The descriptive and analytical approach was followed to collect and extract the data for urban green spaces of Al-Salhia residential complex within Baghdad city that based on six tools for data collection and analysis which were: field survey, climatic factors analysis, urban fabric analysis, personal interviews, cultural factors analysis, and questionnaire. The questionnaire was distributed to a random sample of the people and specialists from Al-Salhia complex residents. After collecting the forms, the data was gathered by the "Excel Office Microsoft" software, and the " System Analysis Statistical" program was used to download the data and the differences between the means were compared with the least significant difference "LSD" test.  The results revealed that the decrement in the green space’s percent of the complex and their efficien. And the shades created by the residential buildings were not taken into consideration by designing the green spaces and their impact.